Mama Training: Pelatihan Emotional Intelligence Untuk Meningkatkan Self-Regulation Guru Sekolah Dasar - Dedi Nasruddin; V. Heru Hariyanto (JIP (Jurnal Intervensi Psikologi), 2022)
The task of the teachers in addition to educating students, they also have a standard of achieving performance targets given by the school. The heavy workload makes the need for good self-regulation on the individual. Self-regulation is related to a series of planning actions that are directed towards realizing the achievement of targets that can improve performance. This training brings emotional intelligence as a variable that can improve self-regulation in elementary primary school teachers. The research design is a one group pre-posttest experimental design. The number of participants who took part in the training was 13 people. The results of this study show that there is a positive correlation of emotional intelligence in improving self-regulation in elementary school teachers